1973
DOI: 10.1099/0022-1317-21-2-215
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-sensitive Poliovirus Mutants Defective in Repression of Host Protein Synthesis are also Defective in Structural Protein

Abstract: SUMMARYWild-type poliovirus (ts +) rapidly represses synthesis of host cell protein (psr+ character), at permissive (37 °C) or restrictive (39"5 °C)temperatures. A search for ts mutants that were psr+ at 37 °C and psr at 39"5 °C was successful when gene expression was minimized by adding guanidine, depleting cystine and avoiding very high input multiplicities. Repressor defects were found in six ts mutants, all of which carry ts defects solely in structural protein. All of the five ts mutants tested that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Also, lysates from poliovirus-infected cells can inactivate eIF-4B when it is added to the lysate (data not shown) or in mixed lysates from infected and uninfected cells. The mechanism of inactivation is not known, but it is presumably carried out by a viral protein (25).…”
Section: Effects Of Initiation Factors In Infected and Uninfectedmentioning
confidence: 99%
“…Also, lysates from poliovirus-infected cells can inactivate eIF-4B when it is added to the lysate (data not shown) or in mixed lysates from infected and uninfected cells. The mechanism of inactivation is not known, but it is presumably carried out by a viral protein (25).…”
Section: Effects Of Initiation Factors In Infected and Uninfectedmentioning
confidence: 99%
“…Alternatively, the picornaviruses appear to require the synthesis of a virus-specified function to arrest the host (1, 6, 25, 36). The possibility that a picornavirus structural component contributes to shutoff has not been completely dismissed (12,27,33). Infection with HSV results in the rapid shutoff of host protein synthesis and is accompanied by dissociation of the polyribosomes (13,34,35).…”
Section: Figmentioning
confidence: 99%
“…Also, infection in the presence of 1 mM guanidine, which prevents detectable viral replication and translation, does not seem to affect host cell shutoff at higher multiplicities of infection (MOIs) (7,16). Using temperature-sensitive mutants to examine this problem, Steiner-Pryor and Cooper (20) showed that the ability to inhibit host cell protein synthesis seems to map in the region of the structural protein genes. However, Cole and Baltimore demonstrated that defective interfering polio virions are able to inhibit host cell translation despite the fact that their defectiveness originated because of deletions in the capsid genes and resulted in an inability to specify for structural proteins (3).…”
mentioning
confidence: 99%